BRAF mutation in papillary thyroid cancer—Prevalence and clinical correlation in a South‐East Asian cohort. (28th November 2018) - Goh, Xueying; Lum, Jeffery; Yang, Samantha Peiling; Chionh, Siok Bee; Koay, Evelyn; Chiu, Lily; Parameswaran, Rajeev; Ngiam, Kee Yuan; Loh, Thomas Kwok Seng; Nga, Min En; Lim, Chwee Ming
Abstract : Objective: BRAF mutation is the commonest mutation seen in papillary thyroid cancer (PTC), but its prevalence and clinical significance vary across countries. We aim to evaluate the prevalence and clinico‐pathological correlation of BRAF mutation in PTC patients at our centre. Study Design: Retrospective cohort study of 75 consecutive archival thyroid specimens, whereby BRAF mutation was detected using a polymerase chain reaction (PCR) technique and correlated with clinical and pathological features and outcomes. Setting: Tertiary university hospital in Singapore. Participants: A total of 75 consecutive histologically proven archival thyroid specimens from patients who underwent thyroidectomy for PTC were accrued for this study. Main outcome measures: Main outcome is to determine the prevalence of the BRAF mutation in our South‐East Asian population. Secondary aim is to correlate the mutational status with adverse pathological features like histological variants, multi‐focality, lymphovascular invasion and extra‐thyroidal extension, clinical features like demographics, TNM stage, recurrence and survival, as well as treatment details like type of surgery performed and radioiodine doses. Results: BRAF mutation was detected in 56% (42/75) of PTC. All but one BRAF‐mutated PTC had the BRAFV600E mutation. BRAF‐mutated tumours were associated with an advanced T‐stage ( P = 0.049) and were more likely to have a central neck dissection ( P = 0.036). There was no significant correlation between BRAF mutation status and clinical outcomes. Conclusion: The prevalence of BRAF mutation is 56%. BRAF mutation‐positive tumours were associated with locally advanced disease, but not poorer survival.